The Utilization of Moringa Seeds (Moringa oleifera [Lam]) Extracts as a Coagulant Alternative on Purification of Drinking Water - Godevridus Tiser (Journal of Applied Chemical Science, 2012)
There have been done research utilization moringa seed (moringa oleifera [lam]) extracts as a coagulant alternative to purify a drinking water. The water sample was taken from the Oeneke Springs at the Nort Middle Timor district. The method used in this study is the jar test method. The moringa seed extracts could act as a natural coagulant that was able to replace the synthetic coagulants such as aluminum sulfate. The moringa seed extracts could reduce the average turbidity of 2.23 NTU with a provision of 96.3%, the average suspended solids 173.3 mg/L and 58.33% provision for suspended solids, total hardness average of 87.73 mg/L and 17.54% of total allowance for hardness, total solids average of 306.67 mg/L and 41.03% total solids allowance, the average total dissolved solids average 213.33 mg/L and 42.45% soluble solids stage with optimum dose of coagulant Moringa seeds is 25 ppm, while Aluminum sulfate can decrease rara average turbidity of 1.25 NTU with allowance for 97.93%, the average suspended solids 137.33 mg/L with allowance 66.99%, total hardness average of 82.13 mg/L and 22.81% of total allowance for hardness, total solids average of 213.33 mg/L and 72.885 preliminary total solids, total dissolved solids averaged 76 mg/L and 79.5% of total dissolved solids stage with optimum dose of coagulant is Aluminium Sulphate 100 ppm. Overall, moringa seeds could be used as an alternative biokoagulant in drinking water purification process.